The equation x^2 + 5x +2=0 has to be solved. The solutions of the quadratic equation ax^2 + bx + c = 0 are x1 = `(-b + sqrt(b^2 - 4ac))/(2a)` and x2 = `(-b - sqrt(b^2 - 4ac))/(2a)`
For x^2 + 5x +2=0
x1 = `(-5 + sqrt(25 - 8))/2`
=> `-5/2 + sqrt 17/2`
x2 =` -5/2 - sqrt 17/2`
The approximate solutions of the equation x^2 + 5x +2=0 are -0.4384 and -4.5615
In order to solve the equation (x^2)+5x+2, you should first observe that you will need to factor. There is no immediately obvious way to factor, so you need to use the quadratic equation to factor. Remember that the quadractic equation is as follows: for For ax2 + bx + c = 0. For the equation you provided, a=1 because the coefficient in front of the x^2 is 1, b=5, and c=2. Using this information, plug it into the quadratic equation and you will get: x=-5+/-sqrt((5^2)-4*1*2)/2*1. Write this as two equations separating the +/-. Solve both and you will get -4.56 and -0.44 as your two answers.